ANALISIS PENGARUH KUALITAS PEMBIAYAAN TERHADAP MINAT NASABAH GRIYA IB HASANAH - Nita Nugraeni Rivai; Fajri Ryan; Siti Mardiah (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2023)
Financing Quality is the risk associated with the bank's condition, and customer compliance with financing obligations to pay yields, repay, and return financing to the bank determines the quality of bank financing. The method used is multiple linear regression research (quantitative); this study uses an online questionnaire with a sample of 53 customers to analyze data. By carrying out research instruments using validity tests, reliability tests, multiple regression tests, classical assumption tests, hypothesis tests (f-test and t-test) and the coefficient of determination (r). The results of this study stated that the simultaneous test, namely Price, service seven promotions significantly positively affected Griya Ib Hasanah customer interest (H1) was accepted, Price, namely the second hypothesis (H2) was rejected, did not significantly affect Griya Ib Hasanah customer interest taken from SPSS data 26. The third hypothesis (H3), namely, service received, significantly affects the interest of Griya IB Hasanah customers. Finally, the promotion of the fourth hypothesis (H4) is accepted, significantly influencing the interest of Griya Ib Hasanah customers, which in the statistical test Prob is 0.038 < α = 0.05.